North Perth Community Sport Hub: An initiative to Improve Health and Well-being in Scotland - Saroh, Siti Mei (BKM Public Health and Community Medicine, 2024)
Purpose: This initiative strives to provide children with access to high-quality community sport, fostering lifelong enjoyment and appreciation for the inherent value of physical activity. Content: The program delivers a diverse range of sporting and physical activity opportunities within local communities. Notably, it emphasizes inclusivity and accessibility, aiming to overcome barriers to participation such as transportation costs, confidence levels, prior experience, fitness levels, age, gender, childcare needs, and health concerns. Furthermore, the initiative incorporates healthy cooking lessons, creating a holistic approach to family well-being. The impact of this program are increased family participation, and facilitated a more cohesive approach to collaboration among partner organizations with shared objectives The challenges are complexities in project management and evaluation due to many external collaboratin, uneven resource distribution among participating sports clubs, and limitations associated with unfamiliar venues. Conclusion: Moving forward, the initiative seeks to incorporate stronger sports clubs and explore the potential for transitioning leadership to a parent-led community group. This approach aims to ensure the program's long-term sustainability and enhance its ability to effectively address the specific needs of diverse communities within North Perth.